Influência da interação social nas respostas motoras de ratos submetidos a um modelo de dor inflamatória e o comportamento pró-social do seu coabitante - Silva, Kelly Coutinho da (2017)
The affective-motivational component of pain refers to the effects of experiencing pain on emotions and behavior. Studies suggest that social contact induces changes in nociceptive and affective responses in individuals with pain. Motor activity as a parameter for pain assessment in both animals and humans has already been used in some studies, but the association of these variables with social components has not yet been tested. In addition, most of the studies related to nociception are directed to the subject who is in an allergic condition, and his or her contacts end up becoming coadjuvant. Our objective was to evaluate how social contact interferes in the motor activity of rats submitted to a model of inflammatory pain and the pro-social behavior of their contacts. We used 42 Wistar rats, 2 to 3 months old. For this, two experiments were performed, in all of them the n = 6 animals per group. In the experiment I was evaluated the behavior of resident mouse during contact with control animals (CTRL), saline (SAL) and with inflammatory pain (FORM). For this, the latency time for the first contact and the duration of the contact were measured over 20 min. The inflammatory pain did not alter the latency time of the first contact of the residents with the control animals. However, the duration of contact was higher with animals of the FORM group when compared to the CTRL group and the SAL group. In experiment II the effect of social contact in the motor response of the animals with inflammatory pain was evaluated. The animals were divided into four groups: Formalin Isolate (FI) that received formalin and then was isolated, Formalin Contact (FC) that received formalin and had contact with the animal from the box where it resided, Control Contact (CC) that was only Manipulated and put in contact with the resident and the Isolated Control (CI) that has been manipulated and placed in isolation. After 20 min of contact or isolation, the video of the animals was analyzed in the ANY-maze to verify the motor activity. The behaviors analyzed were: total distance traveled, rearing time, number of outflows of quadrants and immobility time, during the total time of the test and divided in intervals of 5 minutes making 4 blocks. The animals of the FC group presented less rearing time and number of exits of the quadrants in relation to the CI. On the other hand, the FI animals had less time rearing and exit of the quadrants in relation to the CI, and a longer time of immobility in relation to all the other groups. When analyzed by time block there was a difference in the interval of 0 to 5 minutes for the distance traveled between CC and FC, and CC and FI, in which the CC animals moved more during the test. The rearing time was higher for the CC and CI animals compared to the FC and FI in the range of 0 to 5, in the second interval the CI group had a longer rearing time than the FC and in the third interval there was a longer time of the CI rats in Relation to CF and FI. There was longer immobility time of the FI animals in relation to all the other groups in the range of 0 to 5 min. It was observed that the social interaction preserved the motor activity of the FC rats, but not the FI compared to their controls. In addition, the resident animal could differentiate the nociceptive conditions of the cohabitant, and this resulted in a longer time of interaction between these animals and the adopted social behavior.